LIVING HADIS DALAM DINAMIKA GERAKAN SOSIAL: STUDI PENGAJIAN HADIS DI MASJID AL-MUSTAQIM BUNGGUL - ANA ISTIANA; IANATUSSOLEH; HIDAYATURRAHMAH; MASRUROH; IMROATUL ISLAMIA; FATICHATUS SA’DIYAH (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This study examines the phenomenon of living hadith through the form of hadith study sessions held at Al-Mustaqim Mosque in Bunggul Village, Tlagah, Galis, Bangkalan. The study is a community-driven initiative that began during Ramadan 2020, aimed at deepening the understanding of the Sunnah of Prophet Muhammad (peace be upon him). This research uses a qualitative method with a phenomenological approach, employing observation and interviews as primary data collection techniques, and documentation as secondary data. The study sessions are held regularly every Tuesday night using the wetonan method and focus on the Kutub al-Sittah, as well as on exegesis (tafsir) and theology (tawḥīd). The main hadith that serves as the foundation for the study is the Prophet’s saying about the virtues of consistent deeds. This hadith is analyzed through classical commentaries by scholars such as al-Nawawi, Ibn Hajar al-‘Asqalani, and al-Ghazali. The findings of this research indicate that the study sessions represent a grassroots social movement that has successfully shaped a new pattern of religious practice, despite facing social dynamics including resistance from some members of the community. In response to these challenges, the researcher formulates the research problems in relation to the activities at Al-Mustaqim Mosque, which include: the religious activities conducted at the mosque, the historical background of the study sessions, the process of the study sessions, and the analysis of hadith used in the sessions. This study is a type of field research. The strengthening of hadith legitimacy, the integration of local traditions (such as the choice of Wednesday night), and the wetonan method make this program a model of text- and context-based da'wah that effectively shapes the religious character of the community. This research shows that living hadith is not only a spiritual practice but also a means of social and cultural transformation within rural Muslim communities